Pengelolaan Sampah Dalam Upaya Mitigasi Bencana Alam Di Desa Seriwe Kecamatan Jerowaru Lombok Timur - Pendi Rosadi; Wahyu; Nurhasanah; Via Franciska Yolanda Putri; I Putu Artayasa (Universitas Mataram, 2022)
The presence of garbage in the coastal area of ​​Seriwe Village is a problem that needs to be solved immediately. Management and utilization of organic and inorganic waste is important to minimize the amount of waste and mitigate natural disasters. This community service aims to provide education to the community about the negative impact of garbage accumulation in Seriwe Village, especially in the coastal area. The second goal is to provide education on how to handle waste and explain the types of waste that can be used as goods that are useful and have economic value. This community service is carried out by applying the methods of interview, observation, and counseling. Interview and observation methods were carried out to find out how the community handled waste, while counseling was carried out to explain how to manage and utilize organic and inorganic waste. This community service was carried out by Mataram University students who programmed the Integrated Real Work Lecture in Seriwe Village, while the participants were 50 people from Seriwe Village. The results of community service show that of the 50 people interviewed, only 8% of respondents have temporary garbage collectors and do waste sorting, while 92% of respondents do not have one and do not sort their waste. The results of the interview also show that 20% of the Seriwe Village community have used waste into materials of economic value. The conclusion of this activity is that this community service provides the benefit of increasing public awareness about the negative impacts and how to handle waste so as to provide benefits to the Seriwe Village community.